Performance evaluation of Epoxy-60% zinc coating for steel bridge decks: physical properties analysis and optimal application window determination - Tang, Linwei; Mao, Nongping; Wan, Kai; Xiong, Xuetang; Chen, Bo; Li, Weixiong (Frontiers in Materials, 2025)
Evaluating the performance of epoxy-60% zinc coatings on steel bridge decks is essential for determining the optimal construction window to ensure long-term corrosion resistance and preventing delamination of overlay layers. The research systematically assessed the curing process, environmental exposure effects, and interlayer bonding strength of the epoxy-60% zinc coatings. Curing characteristics were analyzed, revealing that full curing is achieved within 7.5–8 days at 25 °C, while bonding strength significantly decreases after 60 days of natural environmental exposure. The effect of surface cleaning before applying the waterproof bonding layer was also examined, showing a substantial enhancement in bonding strength. The findings indicate that epoxy-60% zinc coating provides effective protection against corrosion and maintains structural integrity when applied within 60 days of curing. It is recommended to limit environmental exposure to no more than 60 days, with regular monitoring and proper surface preparation ensuring optimal performance. These insights contribute to understanding the performance of epoxy-60% zinc coatings and offer valuable guidelines for their application on steel bridge decks.